Description of the morpho- functional characteristics of junior tennis players - Celis, J. M. (Coaching and Sport Science Review, 2018)
The description of the morpho-functional characteristics of junior tennis players through basic and easy to access protocols that evaluate relevant aspects for performance in tennis, help the development and evolution of physical conditioning and sport training.